Reassortant strains of Rotavirus A (Sedoreoviridae: Rotavirus: Rotavirus A): the role of animal rotaviruses in the emergence of new human rotavirus variants - Elena I. Velikzhanina; Tatiana A. Sashina; Nadezhda A. Novikova (Вопросы вирусологии, 2025)
Animal rotaviruses (RV) play a significant role in the formation of new variants of epidemiologically significant human group A rotavirus (RVA) strains.A reassortant variant of genotype G3P[8] which has been shown to originate from RV in horses and cattle currently dominates on the territory of the Russian Federation. In addition, reassortant RV variants of genotypes G3P[3], G3P[9], G6P[9], similar to RV of cats and dogs, have been sporadically identified in the world for a long time. Given the relevance of this topic, a detailed study of the AU-1-like genetic group of RVAs, whose representatives are closely related to animal RVs, particularly those found in cats and dogs, is of scientific and practical interest.